Geochemical signatures and magmatic processes of Bindiba granitoids: Neoproterozoic crustal evolution of the central domain of the Pan-African fold belt - Jacques W. Wassouo; Abakar Mahamat; Amadou D. Kepnamou; fodoué Yaya; Yvan D. Ntomb; Eugène P.B. Mandeng; Nguihdama Dagwai; Ngounouno Isamaila (Journal of African Earth Sciences, 2026)

Temporal Variability of the 0°C Isotherm Height Over the Coast of the Biobío Region (36.8° S), Chile: Characterisation and Case Studies - Camila Quijada‐Meza; Martín Jacques‐Coper; René D. Garreaud; Simone Schauwecker (International Journal of Climatology, 2026)
We analyse inter‐annual, monthly, synoptic and sub‐daily variability aspects of the 0°C isotherm height (H0), using ERA5 reanalysis, observations and estimates, over the coast of the Biobío Region, Chile (36.8° S, 73° W). As this region lacks radiosonde‐based H0 measurements, we use hourly H0 observations onboard aircraft taking off and landing at the Carriel Sur International Airport (SCIE, 36.77° S, 73.06° W) between 2017 and 2019. The validation of ERA5 using observations reveals an excellent performance of this reanalysis in resolving observations. H0 varies throughout the year, reaching a maximum in January and a minimum in July. Then, we estimate H0 for 2022 and 2023 based on Micro Rain Radar data acquired at the Atmospheric River Observatory in Concepción, which has high vertical and temporal resolution. We use vertical profiles of fall velocity and hydrometeor reflectivity during precipitation events. Fall velocity increases on average from ~2.3 to ~4.0 m/s within 300 m just below H0, indicating the presence of melting hydrometeors. Hence, for precipitation storms, it is possible to determine the height of the melting layer (also known as the bright band), which, in turn, enables the estimation of H0. These events show a fair agreement with H0 values from ERA5. Particularly in winter, this region is exposed to hydrometeorological events caused by mid‐latitude synoptic activity. Atmospheric rivers are responsible for up to ~50% of the total annual precipitation and can induce extreme precipitation in some cases. Therefore, three precipitation events are analysed to study their associated synoptic patterns, and the evolution of their respective H0 values. These events correspond to those days for which the highest H0, the lowest H0 and the maximum amount of precipitation were registered.

The role of pondscapes in supporting identities - Lluís Benejam; Jacques-Aristide Perrin; Malgorzata Blicharska; Sandra Brucet; Deniz Başoğlu; Meryem Beklioglu; Aurelie Boissezon; Dani Boix; Maite Colina; Thomas Alexander Davidson; Pieter Lemmens; Alejandro López-de Sancha; et al. (Hydrobiologia, 2026)
This study investigates how pondscapes, networks of ponds, and their surrounding environments contribute to supporting identities across diverse cultural contexts. Supporting identities is a non-material Nature’s Contribution to People referring to people’s sense of place, belonging and connection to nature. We draw on data on landscape features from 17 pondscapes across eight countries in Europe and South America, along with over 700 questionnaire responses. We assessed whether certain landscape features are associated with the perceived delivery of supporting identities and examined how personal characteristics, individual perspectives, and engagement in different activities shape people’s perceptions. Our findings indicate that the perceived delivery of supporting identities emerges from a combination of social and ecological factors rather than from landscape features alone. Although pondscape characteristics showed weak direct effects, pondscapes in warmer climates and with a higher proportion of natural land cover might be associated with a stronger sense of identity. In addition, a strong personal connection to nature and engagement in nature-based activities (wildlife watching, picnicking, hunting), were key pathways shaping perceptions, highlighting that identity-related benefits are context dependent and socially mediated. By integrating ecological and social dimensions, our study highlights the importance of incorporating non-material values into conservation and landscape management strategies.

Boron isotope fractionation during adsorption on aragonite and calcite in artificial seawater and NaCl aqueous solutions - Giuseppe D. Saldi; Pascale Louvat; Frank Heberling; Vasileios Mavromatis; Jacques Schott (Geochimica et Cosmochimica Acta, 2026)

Thirty years of arboreal wildlife trends in an African rainforest under evolving threats and researchers' presence - Bastien Dehaudt; Ruksan Bose; Jean Jacques Avoto; Stephanie Brittain; Tom Bruce; Emily K. Chen; Francis A. Forzi; Britta D. Hardesty; Kimberly M. Holbrook; Aaron M. Lamperti; V. Thomas Parker; John R. Poulsen; et al. (Biological Conservation, 2025)

Scoring adherence to voluntary restriction diets (SAVoReD) in the ADAPT study - Suzannah Gerber; Paul F. Jacques; Kara Livingston Staffier; Micaela C. Karlsen; Susan B. Roberts; Sara C. Folta; Christina D. Economos; Nicola M. McKeown (Appetite, 2025)

Drinking to the last drop! Record of honeydew consumption by a ghost spider (Araneae: Anyphaenidae) in an urban environment in southeastern Brazil - Glauco C.S. Oliveira; Guilherme R. Demetrio; Gabriel C. Jacques; Igor H. Silva; Marcos M. Souza; Antonio D. Brescovit (Food Webs, 2025)

Oral Treatment with Saccharomyces cerevisiae CNCM I-3856 Mitigates the Inflammatory Response Experimentally Induced by Salmonella enterica subsp. enterica Serovar Typhimurium in Mice - Lara L. Campos; Samantha R. M. Oliveira; Maisa N. S. Amaral; Bruno Gallotti; Aline F. Oliveira; Rosa M. E. Arantes; Samantha Ribeiro-Souza; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Flaviano S. Martins (Probiotics and Antimicrobial Proteins, 2025)

Enhancing the Nektar++ spectral/hp element framework for parallel-in-time simulations - Jacques Y. Xing; Chris D. Cantwell; David Moxey (Computer Physics Communications, 2025)

Deep-time history of primate behavior and ecology as revealed by ancestral state reconstructions - Jeffrey K. Spear; Eva A. Hoffman; Juri A. Miyamae; Christopher D. Whalen; Alyssa M. Arre; Chloe Chen-Kraus; Margaret K. Corley; Matteo Fabbri; Jacques A. Gauthier; Michael Hanson; Amanda Leiss; Nicolás Mongiardino Koch; et al. (Journal of Mammalian Evolution, 2025)

Genetic differentiation in Khaya Ivorensis A. Chev., a threaten tree of evergreen African rainforests - Gaël U. D. Bouka; Charles Doumenge; Marius R. M. Ekué; Jérôme Duminil; Jacques Florence; Bernd Degen; Jean Joël Loumeto; Doyle McKey; Olivier J. Hardy (Tree Genetics & Genomes, 2024)

Observing fish behavior in towed fishing gear—is there an influence of artificial light? - Jesse Brinkhof; Manu Sistiaga; Bent Herrmann; Junita D. Karlsen; Eduardo Grimaldo; Nadine Jacques; Zita Bak-Jensen (Reviews in Fish Biology and Fisheries, 2024)
Fish behavior is important to consider when developing selective fishing gear. In studies designed to investigate the size selective properties of towed fishing gears such as trawls, fish behavior is mainly documented by underwater video recordings. Because fishing gear can be operated at great depths or in other low light environments, artificial light is often required for underwater recordings. However, artificial light can influence fish behavior, which casts doubt on the validity of behavioral observations obtained in the presence of artificial light. However, removing artificial light disables video recordings and the possibility to study fish behavior in relation to selectivity devices towed fishing gears in low light environments. To date, little is known about the extent to which artificial light used for video observations affects fish behavior with respect to fishing gear. Therefore, we conducted fishing trials in the Barents Sea demersal trawl fishery to assess the effect of light sources on fish behavior by using size selectivity results in towed fishing gears. We found that the behavior of cod ( Gadus morhua ) was unaffected by the light sources, whereas the behavior of haddock ( Melanogrammus aeglefinus ), saithe ( Pollachius virens ) and redfish ( Sebastes spp.) significantly changed when red light and white light were employed. Our results also demonstrated significant differences in fish behavior between white and red light.

Predicting the Effects of Ozone on Long‐Term Growth of Aspen Trees Using Response Functions Developed From Seedlings Grown in Field Chambers - Jeffrey D. Herrick; S. Douglas Kaylor; Jean‐Jacques B. Dubois (Global Change Biology, 2024)
Tropospheric ozone (O 3 ) is among the most pervasive and harmful air pollutants known to affect ecosystems. In the United States, the Environmental Protection Agency and other agencies are tasked with protecting plants and ecosystems from harmful O 3 exposures. Controlled exposure experiments conducted in field open‐top chambers (OTCs) with small tree seedlings have been used to estimate empirical models of tree growth in response to O 3 exposure for more than 16 species. While this experimental method makes it possible to obtain detailed exposure‐response data, it remains uncertain whether predictions of empirical models parameterized using those data are sufficiently accurate when applied to trees grown in uncontrolled natural environments for long periods. We used O 3 exposure‐response relationships developed from several OTC studies of trembling aspen ( Populus tremuloides Michx.) seedlings to predict the growth of the same species in the Aspen FACE “free‐air” O 3 exposure experiment in Rhinelander, Wisconsin, over 11 years. We acquired individual tree growth data and hourly O 3 exposure from the ambient and elevated O 3 plots in the Aspen FACE experiment, computed annual exposure using the same metrics of O 3 exposure as were used in the OTC seedling experiments, and generated predictions of growth in the Aspen FACE exposures. A simple empirical model parameterized using the OTC seedling data accurately predicted the percent above‐ground biomass loss due to O 3 exposure in the Aspen FACE trees for all 11 years. In the Aspen FACE experiment, the effect of O 3 exposure was established in early years and continued to be observed in later years without worsening. Our study suggests that O 3 exposure‐response relationships obtained from OTC seedling studies can be used to make inferences about effects on larger trees. These results imply that researchers can use these relationships with confidence when estimating risks of O 3 pollution across the United States.

Electric buses as an air pollution and meteorological observation network: Methodology and preliminary results - Daniel L. Mendoza; Andres Gonzalez; Alexander A. Jacques; Colin M. Johnson; Peter T. Whelan; John D. Horel (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mechanisms controlling albite dissolution/precipitation kinetics as a function of chemical affinity: New insights from experiments in 29Si spiked solutions at 150 and 180 °C - Jacques Schott; Giuseppe D. Saldi; Chen Zhu; Lei Gong; Kaiyun Chen (Geochimica et Cosmochimica Acta, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

New Neanderthal remains from Axlor cave (Dima, Biscay, northern Iberian Peninsula) - Shara E. Bailey; Tom W. Davies; Mykolas D. Imbrasas; Talia Lazuen; Jean-Jacques Hublin; Jesus González-Urquijo (Journal of Human Evolution, 2024)

Gallium isotope fractionation during precipitation of α-GaOOH from aqueous solution - Wei Yuan; Zhengrong Wang; Giuseppe D. Saldi; Hongming Cai; Wang Zheng; Jacques Schott; Jiubin Chen (Chemical Geology, 2024)

Evaluation of the Treatment with Akkermansia muciniphila BAA-835 of Chemotherapy-induced Mucositis in Mice - Ramon O. Souza; Vivian C. Miranda; Mônica F. Quintanilha; Bruno Gallotti; Samantha R. M. Oliveira; Janayne L. Silva; Jacqueline I. Alvarez-Leite; Luís C. L. Jesus; Vasco Azevedo; Kátia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2024)

Cues of uncommon food habits within dung beetles: Notes from a seasonally dry tropical forest in South America - Luis Javier Fuentes-Jacques; Renato Portela Salomão; Jose D. Rivera-Duarte; Leonardo Vilas-Bôas M.P. De Cerqueira; Mario E. Favila (Journal of Arid Environments, 2023)

Evaluation of a Functional Craft Wheat Beer Fermented with Saccharomyces cerevisiae UFMG A-905 to treat Salmonella Typhimurium infection in mice - Samantha R. M. Oliveira; Lara L. Campos; Maisa N. S. Amaral; Bruno Galotti; Mayra F. Ricci; Katia D. Vital; Ramon O. Souza; Ana Paula T. Uetanabaro; Mateus S. Junqueira; Andreia M. Silva; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Detection and characterization of wind-blown charged sand grains on Titan with the DraGMet/EFIELD experiment on Dragonfly - Audrey Chatain; Alice Le Gall; Jean-Jacques Berthelier; Ralph D. Lorenz; Rafik Hassen-Khodja; Jean-Pierre Lebreton; Tom Joly-Jehenne; Grégoire Déprez (Icarus, 2023)

Bifidobacterium longum subsp. longum 51A Attenuates Signs of Inflammation in a Murine Model of Food Allergy - Spencer S. Santos; Vivian C. Miranda; Luísa M. Trindade; Valbert N. Cardoso; Diego C. Reis; Geovanni D. Cassali; Jacques R. Nicoli; Denise C. Cara; Flaviano S. Martins (Probiotics and Antimicrobial Proteins, 2023)

Toward a common approach for assessing the conservation status of marine turtle species within the european marine strategy framework directive - Fanny Girard; Alexandre Girard; Jonathan Monsinjon; Antonella Arcangeli; Eduardo Belda; Luis Cardona; Paolo Casale; Sidonie Catteau; Léa David; Florence Dell’Amico; Delphine Gambaiani; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Environmental policies, including the European Marine Strategy Framework Directive (MSFD), generally rely on the measurement of indicators to assess the good environmental status (GES) and ensure the protection of marine ecosystems. However, depending on available scientific knowledge and monitoring programs in place, quantitative GES assessments are not always feasible. This is specifically the case for marine turtle species, which are listed under the Biodiversity Descriptor of the MSFD. Relying on an expert consultation, the goal of this study was to develop indicators and a common assessment approach to be employed by European Union Member States to evaluate the status of marine turtle populations in the frame of the MSFD. A dedicated international expert group was created to explore and test potential assessment approaches, in coherence with other environmental policies (i.e. Habitats Directive, OSPAR and Barcelona Conventions). Following a series of workshops, the group provided recommendations for the GES assessment of marine turtles. In particular, indicators and assessment methods were defined, setting a solid basis for future MSFD assessments. Although knowledge gaps remain, data requirements identified in this study will guide future data collection initiatives and inform monitoring programs implemented by EU Member States. Overall this study highlights the value of international collaboration for the conservation of vulnerable species, such as marine turtles.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Purines help determine the gut’s sweet tooth - Jacques Gonzales; Brian D. Gulbransen (Purinergic Signalling, 2022)

Antarctic Strain of Rhodotorula mucilaginosa UFMGCB 18,377 Attenuates Mucositis Induced by 5-Fluorouracil in Mice - Joana O. P. A. Coutinho; Mônica F. Quintanilha; Marina R. A. Campos; Enio Ferreira; Graciéle C. A. de Menezes; Luiz H. Rosa; Carlos A. Rosa; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Fabiana C. P. Tiago; et al. (Probiotics and Antimicrobial Proteins, 2022)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Effects of combined THC and heroin vapor inhalation in rats - Arnold Gutierrez; Jacques D. Nguyen; Kevin M. Creehan; Mehrak Javadi-Paydar; Yanabel Grant; Michael A. Taffe (Psychopharmacology, 2022)

Correction to: Foraging grounds of adult loggerhead sea turtles across the Mediterranean Sea: key sites and hotspots of risk - Vasiliki Almpanidou; Vasiliki Tsapalou; Anastasia Chatzimentor; Luis Cardona; Françoise Claro; Patrice Hostetter; Yakup Kaska; Wenhua Liu; Jérémy Mansui; Anastasia Miliou; Guido Pietroluongo; Jacques Sacchi; et al. (Biodiversity and Conservation, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Foraging grounds of adult loggerhead sea turtles across the Mediterranean Sea: key sites and hotspots of risk - Vasiliki Almpanidou; Vasiliki Tsapalou; Anastasia Chatzimentor; Luis Cardona; Françoise Claro; Patrice Hostetter; Yakup Kaska; Wenhua Liu; Jérémy Mansui; Anastasia Miliou; Guido Pietroluongo; Jacques Sacchi; et al. (Biodiversity and Conservation, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Chito-oligosaccharide production by chitinase of Streptococcus macrosporeus VTCC 940003 and their inhibition activities on Botrytis cinerea - T. T. V. Anh; N. Q. Uyen; D. V. Hop; Jacques Dommes; Marie-France Versali; Vinh Van Hoang (European Journal of Plant Pathology, 2021)

A benchmark for soil organic matter degradation under variably saturated flow conditions - M. Jia; D. Jacques; F. Gérard; D. Su; K. U. Mayer; J. Šimůnek (Computational Geosciences, 2021)

Longitudinal patterns and linkages in benthic fine particulate organic matter composition, respiration, and nutrient uptake - James M. Hood; Lyndsie M. Collis; John D. Schade; Rebecca A. Stark; Jacques C. Finlay (Limnology and Oceanography, 2021)
Longitudinal changes in the structure and function of river ecosystems have long been recognized, yet our understanding of how such patterns shape elemental cycles remains limited. In particular, while benthic fine particulate organic matter (POM, 0.7–1000 μm) may control many stream nutrient cycles, less is known about longitudinal patterns or controls of benthic POM‐associated nutrient uptake. We conducted a survey of benthic POM‐associated respiration and nutrient uptake as well as microbial biomass (bacteria and algae) and benthic POM composition in four size classes (0.7–53 μm, 53–106 μm, 106–250 μm, and 250–1000 μm) in six streams in the forested South Fork Eel River watershed (California), encompassing a longitudinal gradient in light availability and primary production. Benthic POM at downstream sites was composed of smaller particles with lower organic matter content that were richer in nitrogen and autotrophic material. Areal respiration and nutrient uptake rates increased 11‐ to 67‐fold with stream size. While microbial activity rates did not increase with stream size, benthic POM‐associated microbial biomass increased 20‐fold with stream size, and closely tracked a 15‐fold increase in light availability, and primary production. Thus, microbial biomass, not activity, determined longitudinal patterns in benthic POM‐associated areal nutrient uptake and respiration rates. We attribute longitudinal patterns in microbial biomass to increases in light availability and primary production. Our findings help clarify the role of local (primary production) and upstream processes in shaping ecosystem structure and function.

Genomic diversity and CRISPR‐Cas systems in the cyanobacterium Nostoc in the High Arctic - Anne D. Jungblut; Frédéric Raymond; Moïra B. Dion; Sylvain Moineau; Vani Mohit; Guillaume Quang Nguyen; Maxime Déraspe; Élina Francovic‐Fontaine; Connie Lovejoy; Alexander I. Culley; Jacques Corbeil; Warwick F. Vincent (Environmental Microbiology, 2021)
Summary Nostoc (Nostocales, Cyanobacteria) has a global distribution in the Polar Regions. However, the genomic diversity of Nostoc is little known and there are no genomes available for polar Nostoc . Here we carried out the first genomic analysis of the Nostoc commune morphotype with a recent sample from the High Arctic and a herbarium specimen collected during the British Arctic Expedition (1875–76). Comparisons of the polar genomes with 26 present‐day non‐polar members of the Nostocales family highlighted that there are pronounced genetic variations among Nostoc strains and species. Osmoprotection and other stress genes were found in all Nostoc strains, but the two Arctic strains had markedly higher numbers of biosynthetic gene clusters for uncharacterised non‐ribosomal peptide synthetases, suggesting a high diversity of secondary metabolites. Since viral–host interactions contribute to microbial diversity, we analysed the CRISPR‐Cas systems in the Arctic and two temperate Nostoc species. There were a large number of unique repeat‐spacer arrays in each genome, indicating diverse histories of viral attack. All Nostoc strains had a subtype I‐D system, but the polar specimens also showed evidence of a subtype I‐B system that has not been previously reported in cyanobacteria, suggesting diverse cyanobacteria–virus interactions in the Arctic.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Preliminary results based on geochemical sedimentary constraints on the hydrocarbon potential and depositional environment of a Messinian sub-salt mixed siliciclastic-carbonate succession onshore Crete (Plouti section, eastern Mediterranean) - George Kontakiotis; Vasileios Karakitsios; Jean-Jacques Cornée; Pierre Moissette; Stergios D. Zarkogiannis; Nikolaos Pasadakis; Efterpi Koskeridou; Emmanouil Manoutsoglou; Hara Drinia; Assimina Antonarakou (Mediterranean Geoscience Reviews, 2020)

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

Cellular levels and molecular dynamics simulations of estragole DNA adducts point at inefficient repair resulting from limited distortion of the double-stranded DNA helix - Shuo Yang; Matthias Diem; Jakob D. H. Liu; Sebastiaan Wesseling; Jacques Vervoort; Chris Oostenbrink; Ivonne M. C. M. Rietjens (Archives of Toxicology, 2020)
Estragole, naturally occurring in a variety of herbs and spices, can form DNA adducts after bioactivation. Estragole DNA adduct formation and repair was studied in in vitro liver cell models, and a molecular dynamics simulation was used to investigate the conformation dependent (in)efficiency of N 2 -( trans -isoestragol-3′-yl)-2′-deoxyguanosine (E-3′- N 2 -dG) DNA adduct repair. HepG2, HepaRG cells, primary rat hepatocytes and CHO cells (including CHO wild-type and three NER-deficient mutants) were exposed to 50 μM estragole or 1′-hydroxyestragole and DNA adduct formation was quantified by LC–MS immediately following exposure and after a period of repair. Results obtained from CHO cell lines indicated that NER plays a role in repair of E-3′- N 2 -dG adducts, however, with limited efficiency since in the CHO wt cells 80% DNA adducts remained upon 24 h repair. Inefficiency of DNA repair was also found in HepaRG cells and primary rat hepatocytes. Changes in DNA structure resulting from E-3′- N 2 -dG adduct formation were investigated by molecular dynamics simulations. Results from molecular dynamics simulations revealed that conformational changes in double-stranded DNA by E-3′- N 2 -dG adduct formation are small, providing a possible explanation for the restrained repair, which may require larger distortions in the DNA structure. NER-mediated enzymatic repair of E-3′- N 2 -dG DNA adducts upon exposure to estragole will be limited, providing opportunities for accumulation of damage upon repeated daily exposure. The inability of this enzymatic repair is likely due to a limited distortion of the DNA double-stranded helix resulting in inefficient activation of nucleotide excision repair.

Genetic variants associated with exercise performance in both moderately trained and highly trained individuals - N. R. Harvey; S. Voisin; P. J. Dunn; H. Sutherland; X. Yan; M. Jacques; I. D. Papadimitriou; L. J. Haseler; K. J. Ashton; L. M. Haupt; N. Eynon; L. R. Griffiths (Molecular Genetics and Genomics, 2020)

Understanding ecosystems of the future will require more than realistic climate change experiments – A response to Korell et al. - Hans J. De Boeck; Juliette M. G. Bloor; Rien Aerts; Michael Bahn; Claus Beier; Bridget A. Emmett; Marc Estiarte; José M. Grünzweig; Aud H. Halbritter; Petr Holub; Anke Jentsch; Karel Klem; et al. (Global Change Biology, 2020)
This article is a response to Korell et al., 26, 325–327 ; See also the Commentary on this article by Muller et al., 26, e4–e5 ; See also the response to this Letter to the Editor by Korell et al., 26, 328–329 .

Do nitrogen- and sulphur-remobilization-related parameters measured at the onset of the reproductive stage provide early indicators to adjust N and S fertilization in oilseed rape (Brassica napus L.) grown under N- and/or S-limiting supplies? - Yacine Akmouche; Jeanne Cheneby; Mickael Lamboeuf; Nicolas Elie; Anne Laperche; Jessica Bertheloot; Philippe D’Hooghe; Jacques Trouverie; Jean-Christophe Avice; Philippe Etienne; Sophie Brunel-Muguet (Planta, 2019)

NF1 Somatic Mutation in Dystrophic Scoliosis - Rebecca L. Margraf; Chad VanSant-Webb; Rong Mao; David H. Viskochil; John Carey; Heather Hanson; Jacques D’Astous; Allie Grossmann; David A. Stevenson (Journal of Molecular Neuroscience, 2019)

Effects of Δ9-THC and cannabidiol vapor inhalation in male and female rats - Mehrak Javadi-Paydar; Jacques D. Nguyen; Tony M. Kerr; Yanabel Grant; Sophia A. Vandewater; Maury Cole; Michael A. Taffe (Psychopharmacology, 2018)

Binge-like acquisition of α-pyrrolidinopentiophenone (α-PVP) self-administration in female rats - Mehrak Javadi-Paydar; Eric L. Harvey; Yanabel Grant; Sophia A. Vandewater; Kevin M. Creehan; Jacques D. Nguyen; Tobin J. Dickerson; Michael A. Taffe (Psychopharmacology, 2018)

Tracking metal ions with polypyrrole thin films adhesively bonded to diazonium-modified flexible ITO electrodes - Momath Lo; Abdou K. D. Diaw; Diariatou Gningue-Sall; Jean-Jacques Aaron; Mehmet A. Oturan; Mohamed M. Chehimi (Environmental Science and Pollution Research, 2018)

Differential Spread of Potato virus Y (PVY) Strains O, N:O and NTN in the Field: Implications for the Rise of Recombinant PVY Strains in New Brunswick, Canada - Tyler D. B. MacKenzie; Jacques Lavoie; Xianzhou Nie; Mathuresh Singh (American Journal of Potato Research, 2018)

Characterization of multiple antilisterial peptides produced by sakacin P-producing Lactobacillus sakei subsp. sakei 2a - Kátia G. Carvalho; Felipe H. S. Bambirra; Jacques R. Nicoli; Jamil S. Oliveira; Alexandre M. C. Santos; Marcelo P. Bemquerer; Antonio Miranda; Bernadette D. G. M. Franco (Archives of Microbiology, 2018)

The diversity of ants (Hymenoptera: Formicidae) interacting with the invasive hibiscus mealybug Maconellicoccus hirsutus (Green 1908) (Hemiptera: Pseudococcidae) on ornamental and cultivated plants in Bahia, Brazil - Thamy E. D. Marques; Elmo Borges de Azevedo Koch; Igor Silva dos Santos; José Raimundo Maia dos Santos; Cléa dos Santos Ferreira Mariano; Jacques H. C. Delabie (Arthropod-Plant Interactions, 2018)

Correspondence between δ13C and δ15N in soils suggests coordinated fractionation processes for soil C and N - Jacques A. Nel; Joseph M. Craine; Michael D. Cramer (Plant and Soil, 2018)

The 2017 CALDAR Summer Institute and International Conference Promoting Global Health—Precision Research in Substance Abuse, HIV, and Care - Yih-Ing Hser; Ming D. Li; Christine Grella; Lynn Brecht; Zhiwei Chen; Sulie L. Chang; Linda Chang; Jacques Normand; Betty Tai (Journal of Neuroimmune Pharmacology, 2017)

A review of carotenoid utilisation and function in crustacean aquaculture - Nicholas M. Wade; Jacques Gabaudan; Brett D. Glencross (Reviews in Aquaculture, 2017)
Crustaceans are cultured extensively around the world in intensive farming systems. High‐performance formulated feeds have been developed for crustacean aquaculture, which are often supplemented with a number of natural and synthetic carotenoid sources. Studies over a number of years have consistently shown that dietary carotenoid supplementation is beneficial for crustacean aquaculture across a range of commercially relevant parameters. Most obvious is the effect on pigmentation, where carotenoid inclusion levels in feeds and duration of feeding diets with carotenoids have been optimised across many species to improve product colour, and subsequently quality and price. However, beneficial effects of carotenoid inclusion have increasingly been demonstrated on other parameters. This review updates the recent progress in our understanding of dietary carotenoid utilisation and storage, and the combined effects of diet, genetics and environment on crustacean pigmentation. In addition, the range of other physiological benefits this class of molecules brings to these animals is summarised. These include improvements in survival, growth, reproductive capacity, disease resistance and stress resistance.

Additions to Lindgomyces (Lindgomycetaceae, Pleosporales, Dothideomycetes), including two new species occurring on submerged wood from North Carolina, USA, with notes on secondary metabolite profiles - Huzefa A. Raja; Noemi D. Paguigan; Jacques Fournier; Nicholas H. Oberlies (Mycological Progress, 2017)

Pepo aphid-borne yellows virus: a new species in the genus Polerovirus - Jacques D. Ibaba; Mark D. Laing; Augustine Gubba (Virus Genes, 2017)

Effectiveness of Combined Use of Mineral Oil and Insecticide Spray in Reducing Potato Virus Y (PVY) Spread under Field Conditions in New Brunswick, Canada - Tyler D. B. MacKenzie; Jacques Lavoie; Xianzhou Nie; Mathuresh Singh (American Journal of Potato Research, 2017)

Differential expression and emerging functions of non-coding RNAs in cold adaptation - Jacques J. Frigault; Mathieu D. Morin; Pier Jr Morin (Journal of Comparative Physiology B, 2017)

The extracellular matrix of the oleolytic biofilms of Marinobacter hydrocarbonoclasticus comprises cytoplasmic proteins and T2SS effectors that promote growth on hydrocarbons and lipids - Habiba Ennouri; Paul d'Abzac; Florence Hakil; Priscilla Branchu; Murielle Naïtali; Anne‐Marie Lomenech; Ridha Oueslati; Jacques Desbrières; Pierre Sivadon; Régis Grimaud (Environmental Microbiology, 2017)
Summary The assimilation of the nearly water insoluble substrates hydrocarbons and lipids by bacteria entails specific adaptations such as the formation of oleolytic biofilms. The present article reports that the extracellular matrix of an oleolytic biofilm formed by Marinobacter hydrocarbonoclasticus at n ‐hexadecane–water interfaces is largely composed of proteins typically cytoplasmic such as translation factors and chaperones, and a lesser amount of proteins of unknown function that are predicted extra‐cytoplasmic. Matrix proteins appear to form a structured film on hydrophobic interfaces and were found mandatory for the development of biofilms on lipids, alkanes and polystyrene. Exo‐proteins secreted through the type‐2 secretion system (T2SS) were shown to be essential for the formation of oleolytic biofilms on both alkanes and triglycerides. The T2SS effector involved in biofilm formation on triglycerides was identified as a lipase. In the case of biofilm formation on n ‐hexadecane, the T2SS effector is likely involved in the mass transfer, capture or transport of alkanes. We propose that M. hydrocarbonoclasticus uses cytoplasmic proteins released by cell lysis to form a proteinaceous matrix and dedicated proteins secreted through the T2SS to act specifically in the assimilation pathways of hydrophobic substrates.

Genome sequence analysis of two South African isolates of Moroccan watermelon mosaic virus infecting cucurbits - Jacques Davy Ibaba; Mark D. Laing; Augustine Gubba (Virus Genes, 2016)

Active transposable elements recover species boundaries and geographic structure in Madagascan coffee species - Julissa Roncal; Romain Guyot; Perla Hamon; Dominique Crouzillat; Michel Rigoreau; Olivier N’Guessan Konan; Jean-Jacques Rakotomalala; Michael D. Nowak; Aaron P. Davis; Alexandre de Kochko (Molecular Genetics and Genomics, 2016)

A dynamic leaf gas‐exchange strategy is conserved in woody plants under changing ambient CO 2 : evidence from carbon isotope discrimination in paleo and CO 2 enrichment studies - Steven L. Voelker; J. Renée Brooks; Frederick C. Meinzer; Rebecca Anderson; Martin K.‐F. Bader; Giovanna Battipaglia; Katie M. Becklin; David Beerling; Didier Bert; Julio L. Betancourt; Todd E. Dawson; Jean‐Christophe Domec; et al. (Global Change Biology, 2016)
Rising atmospheric [CO 2 ], c a , is expected to affect stomatal regulation of leaf gas‐exchange of woody plants, thus influencing energy fluxes as well as carbon (C), water, and nutrient cycling of forests. Researchers have proposed various strategies for stomatal regulation of leaf gas‐exchange that include maintaining a constant leaf internal [CO 2 ], c i , a constant drawdown in CO 2 ( c a − c i ), and a constant c i / c a . These strategies can result in drastically different consequences for leaf gas‐exchange. The accuracy of Earth systems models depends in part on assumptions about generalizable patterns in leaf gas‐exchange responses to varying c a . The concept of optimal stomatal behavior, exemplified by woody plants shifting along a continuum of these strategies, provides a unifying framework for understanding leaf gas‐exchange responses to c a . To assess leaf gas‐exchange regulation strategies, we analyzed patterns in c i inferred from studies reporting C stable isotope ratios (δ 13 C) or photosynthetic discrimination (∆) in woody angiosperms and gymnosperms that grew across a range of c a spanning at least 100 ppm. Our results suggest that much of the c a ‐induced changes in c i / c a occurred across c a spanning 200 to 400 ppm. These patterns imply that c a − c i will eventually approach a constant level at high c a because assimilation rates will reach a maximum and stomatal conductance of each species should be constrained to some minimum level. These analyses are not consistent with canalization toward any single strategy, particularly maintaining a constant c i . Rather, the results are consistent with the existence of a broadly conserved pattern of stomatal optimization in woody angiosperms and gymnosperms. This results in trees being profligate water users at low c a , when additional water loss is small for each unit of C gain, and increasingly water‐conservative at high c a , when photosystems are saturated and water loss is large for each unit C gain.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Contralateral cerebello-thalamo-cortical pathways with prominent involvement of associative areas in humans in vivo - Fulvia Palesi; Jacques-Donald Tournier; Fernando Calamante; Nils Muhlert; Gloria Castellazzi; Declan Chard; Egidio D’Angelo; Claudia A. M. Wheeler-Kingshott (Brain Structure and Function, 2015)

The SARAL/AltiKa Altimetry Satellite Mission - Jacques Verron; Pierre Sengenes; Juliette Lambin; Jocelyne Noubel; Nathalie Steunou; Amandine Guillot; Nicolas Picot; Sophie Coutin-Faye; Rashmi Sharma; R. M. Gairola; D. V. A. Raghava Murthy; James G. Richman; et al. (Marine Geodesy, 2015)

Characterization of the 1970s climate shift in South America - Martín Jacques‐Coper; René D. Garreaud (International Journal of Climatology, 2015)
The 1976–1977 cold‐to‐warm sea surface temperature ( SST ) shift in the tropical Pacific Ocean, which has been associated with a phase change of the Pacific Decadal Oscillation ( PDO ) index, separated a ‘La Niña‐like’ decadal regime from an ‘El Niño‐like’ one. In this article, we analyse the differences of mean of annual and austral‐summer ( DJF ) temperature, precipitation, and sea‐level pressure ( SLP ) over South America ( SA ) between 1961–1973 and 1978–1990, and explore the occurrence of significant shifts in their time series. Our sources are instrumental records, gridded interpolated data, and reanalyses. Although major regional differences in the intensity of the signal are detected, the climate shift is identified in all variables. In the mid‐1970s at annual level, reanalysis SLP data reveal the onset of a step‐like anticyclonic circulation anomaly in the southern tip of SA and an abrupt weakening of the Southeast Pacific Subtropical Anticyclone ( SEPA ). This latter feature may have partly induced the rapid warming observed along the tropical–extratropical west coast of the continent through the weakening of the cold Humboldt current system. An abrupt warming was also detected in surface air temperature ( SAT ) composites located along the coast of the northern part of SA and in Southeastern SA ( SESA ). During summer, we found a particularly conspicuous shift‐like warming over Southern South America ( SSA , comprising Patagonia). Besides, a shift‐like increase (decrease) in annual mean precipitation is observed over Central Argentina and in the tropics, to the south (north) of 10°S. In line with previous studies, we conclude that both the interannual (El Niño‐Southern Oscillation, ENSO ) and the interdecadal ( PDO ) variability modes seem to have had an incidence in the manifestation of the 1970s climate shift, and that its magnitude appears to be unprecedented during the 20th century, as shown in particular by century‐long SAT composites from northern Chile and SSA .

Reactive transport codes for subsurface environmental simulation - C. I. Steefel; C. A. J. Appelo; B. Arora; D. Jacques; T. Kalbacher; O. Kolditz; V. Lagneau; P. C. Lichtner; K. U. Mayer; J. C. L. Meeussen; S. Molins; D. Moulton; et al. (Computational Geosciences, 2015)

Climate‐induced changes in host tree–insect phenology may drive ecological state‐shift in boreal forests - Deepa S. Pureswaran; Louis De Grandpré; David Paré; Anthony Taylor; Martin Barrette; Hubert Morin; Jacques Régnière; Daniel D. Kneeshaw (Ecology, 2015)
Climate change is altering insect disturbance regimes via temperature‐mediated phenological changes and trophic interactions among host trees, herbivorous insects, and their natural enemies in boreal forests. Range expansion and increase in outbreak severity of forest insects are occurring in Europe and North America. The degree to which northern forest ecosystems are resilient to novel disturbance regimes will have direct consequences for the provisioning of goods and services from these forests and for long‐term forest management planning. Among major ecological disturbance agents in the boreal forests of North America is a tortricid moth, the eastern spruce budworm, which defoliates fir ( Abies spp.) and spruce ( Picea spp.). Northern expansion of this defoliator in eastern North America and climate‐induced narrowing of the phenological mismatch between the insect and its secondary host, black spruce ( Picea mariana ), may permit greater defoliation and mortality in extensive northern black spruce forests. Although spruce budworm outbreak centers have appeared in the boreal black spruce zone historically, defoliation and mortality were minor. Potential increases in outbreak severity and tree mortality raise concerns about the future state of this northern ecosystem. Severe spruce budworm outbreaks could decrease stand productivity compared with their occurrence in more diverse, southern balsam fir forest landscapes that have coevolved with outbreaks. Furthermore, depending on the proportion of balsam fir and deciduous species present and fire recurrence, changes in regeneration patterns and in nutrient cycling could alter ecosystem dynamics and replace black spruce by more productive mixed‐wood forest, or by less productive ericaceous shrublands. Long‐term monitoring, manipulative experiments, and process modeling of climate‐induced phenological changes on herbivorous insect pests, their host tree species, and natural enemies in northern forests are therefore crucial to predicting species range shifts and assessing ecological and economic impacts.

Moderate oxygen depletion as a factor favouring the filamentous growth of Sphaerotilus natans - Marina Seder-Colomina; Anne Goubet; Sébastien Lacroix; Guillaume Morin; Georges Ona-Nguema; Giovanni Esposito; Eric D. Van Hullebusch; Jean-Jacques Pernelle (Antonie van Leeuwenhoek, 2015)

Fatal Disseminated Infection with Fusarium petroliphilum - Tuba Ersal; Abdullah S. M. Al-Hatmi; Burcu Dalyan Cilo; Ilse Curfs-Breuker; Jacques F. Meis; Fahir Özkalemkaş; Beyza Ener; Anne D. van Diepeningen (Mycopathologia, 2015)

Full-genome analyses of a Potato Virus Y (PVY) isolate infecting pepper (Capsicum annuum L.) in the Republic of South Africa - Vaneson Moodley; Jacques D. Ibaba; Roobavathie Naidoo; Augustine Gubba (Virus Genes, 2014)

Heavy Metal and Arsenic Resistance of the Halophyte Atriplex halimus L. Along a Gradient of Contamination in a French Mediterranean Spray Zone - Jacques Rabier; Isabelle Laffont-Schwob; Anca Pricop; Ahlem Ellili; Gabriel D’Enjoy-Weinkammerer; Marie-Dominique Salducci; Pascale Prudent; Brahim Lotmani; Alain Tonetto; Véronique Masotti (Water, Air, & Soil Pollution, 2014)

To settle or to move? The interplay between two classes of cyclic lipopeptides in the biocontrol strain P seudomonas CMR 12a - Jolien D'aes; Nam Phuong Kieu; Valérie Léclère; Caroline Tokarski; Feyisara Eyiwumi Olorunleke; Katrien De Maeyer; Philippe Jacques; Monica Höfte; Marc Ongena (Environmental Microbiology, 2014)
Summary P seudomonas CMR 12a is a biocontrol strain that produces phenazine antibiotics and as yet uncharacterized cyclic lipopeptides ( CLPs ). The CLPs of CMR 12a were studied by chemical structure analysis and in silico analysis of the gene clusters encoding the non‐ribosomal peptide synthetases responsible for CLP biosynthesis. CMR 12a produces two different classes of CLPs : orfamides B , D and E , whereby the latter two represent new derivatives of the orfamide family, and sessilins A–C . The orfamides are made up of a 10 amino acid peptide coupled to a β‐hydroxydodecanoyl or β‐hydroxytetradecanoyl fatty acid moiety, and are related to orfamides produced by biocontrol strain P seudomonas protegens Pf‐5. The sessilins consist of an 18‐amino acid peptide linked to a β‐hydroxyoctanoyl fatty acid and differ in one amino acid from tolaasins, toxins produced by the mushroom pathogen P seudomonas tolaasii . CLP biosynthesis mutants were constructed and tested for biofilm formation and swarming motility. Orfamides appeared indispensable for swarming while sessilin mutants showed reduced biofilm formation, but enhanced swarming motility. The interplay between the two classes of CLPs fine tunes these processes. The presence of sessilins in wild type CMR 12a interferes with swarming by hampering the release of orfamides and by co‐precipitating orfamides to form a white line in agar.

Trypanocidal and cytotoxic evaluation of synthesized thiosemicarbazones as potential drug leads against sleeping sickness - Bienvenu Glinma; Sika D. S. Kpoviessi; Fernand A. Gbaguidi; Coco N. Kapanda; Joanne Bero; Joëlle Quetin-Leclercq; Mansourou Moudachirou; Jacques Poupaert; Georges C. Accrombessi; Emma W. Gachomo; Lamine Baba-Moussa; Simeon O. Kotchoni (Molecular Biology Reports, 2014)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Photodegradation of methylmercury in stream ecosystems - Martin Tsz Ki Tsui; Joel D. Blum; Jacques C. Finlay; Steven J. Balogh; Sae Yun Kwon; Yabing H. Nollet (Limnology and Oceanography, 2013)
Photodegradation is an important sink for highly toxic methylmercury (MeHg) in aquatic ecosystems. Lakes have been extensively studied for MeHg photodegradation, but much less is known about streams, mainly because of the heterogeneity in sunlight availability along stream reaches and because there has been a lack of tools with which to integrate this longitudinal variability. We utilize odd‐mass anomalies of stable Hg isotopes (i.e., Δ 199 Hg) as a proxy for estimating the relative extent of MeHg photodegradation in streams. In a northern California stream network, levels of MeHg in water and biota increased with increasing stream size in headwater and intermediate streams (drainage areas ranging from 0.6 to 150 km 2 ), but MeHg levels decreased substantially in larger streams (drainage areas up to 1212 km 2 ). In smaller streams, the increase of MeHg levels is attributed to increasing in situ MeHg production and is accompanied by only a small increase in Δ 199 Hg, indicating that the rate of MeHg photodegradation is low relative to the rate of in situ MeHg production. In larger streams, decreasing MeHg levels coincided with significant increases in Δ 199 Hg of MeHg (an average increase of 1.5‰ ± 0.5‰, n = 4), indicating that increasing MeHg photodegradation reduced MeHg levels in these wider, more open channels. Our findings clearly indicate that increasing sunlight availability in stream channels substantially increases MeHg photodegradation, which can reduce MeHg contamination in stream food webs.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Evidence for genetic differentiation and variable recombination rates among Dutch populations of the opportunistic human pathogen Aspergillus fumigatus - CORNÉ H. W. KLAASSEN; JOHN G. GIBBONS; NATALIE D. FEDOROVA; JACQUES F. MEIS; ANTONIS ROKAS (Molecular Ecology, 2012)
As the frequency of antifungal drug resistance continues to increase, understanding the genetic structure of fungal populations, where resistant isolates have emerged and spread, is of major importance. Aspergillus fumigatus is an ubiquitously distributed fungus and the primary causative agent of invasive aspergillosis (IA), a potentially lethal infection in immunocompromised individuals. In the last few years, an increasing number of A. fumigatus isolates has evolved resistance to triazoles, the primary drugs for treating IA infections. In most isolates, this multiple‐triazole‐resistance (MTR) phenotype is caused by mutations in the cyp51A gene, which encodes the protein targeted by the triazoles. We investigated the genetic differentiation and reproductive mode of A. fumigatus in the Netherlands, the country where the MTR phenotype probably originated, to determine their role in facilitating the emergence and distribution of resistance genotypes. Using 20 genome‐wide neutral markers, we genotyped 255 Dutch isolates including 25 isolates with the MTR phenotype. In contrast to previous reports, our results show that Dutch A. fumigatus genotypes are genetically differentiated into five distinct populations. Four of the five populations show significant linkage disequilibrium, indicative of an asexual reproductive mode, whereas the fifth population is in linkage equilibrium, indicative of a sexual reproductive mode. Notably, the observed genetic differentiation among Dutch isolates does not correlate with geography, although all isolates with the MTR phenotype nest within a single, predominantly asexual, population. These results suggest that both reproductive mode and genetic differentiation contribute to the structure of Dutch A. fumigatus populations and are probably shaping the evolutionary dynamics of drug resistance in this potentially deadly pathogen.

The Ecosystem in Practice: Interest and Problems of an Old Definition for Constructing Ecological Models - Jacques Gignoux; Ian D. Davies; Shayne R. Flint; Jean-Daniel Zucker (Ecosystems, 2011)

The Contribution of Raman Scattering to the Fluorescence of the Polyene Antibiotic Amphotericin B - Jacques Bolard; Monique Chéron; John D. Cleary; Robert E. Kramer (Journal of Fluorescence, 2011)

Evaluation of in vitro antagonism and of in vivo immune modulation and protection against pathogenic experimental challenge of two probiotic strains of Bifidobacterium animalis var. lactis - Ariane K. S. Martins; Flaviano S. Martins; Danielle A. Gomes; Samir D. A. Elian; Angélica T. Vieira; Mauro M. Teixeira; Denise C. Cara; Regina M. D. Nardi; Jacques R. Nicoli (Archives of Microbiology, 2010)

Mitochondrial genomic divergence in coelacanths (Latimeria): slow rate of evolution or recent speciation? - Sudarto; Xandramaya C. Lalu; Janny D. Kosen; Agus H. Tjakrawidjaja; Ruby Vidia Kusumah; Bambang Sadhotomo; Kadarusman; Laurent Pouyaud; Jacques Slembrouck; Emmanuel Paradis (Marine Biology, 2010)

Metagenomic profiling of Arctic microbial mat communities as nutrient scavenging and recycling systems - Thibault Varin; Connie Lovejoy; Anne D. Jungblut; Warwick F. Vincent; Jacques Corbeil (Limnology and Oceanography, 2010)
By way of metagenomics and high‐throughput pyrosequencing, we addressed the hypothesis that cyanobacterial mats in polar aquatic ecosystems maintain a nutrient‐rich microenvironment via decomposition and scavenging processes. Analysis of more than 592,554 genomic deoxyribonucleic acid (DNA) reads (total of 11.5 million base pairs) showed that the ribosomal and protein‐coding genes of two High Arctic ice‐shelf mat communities were dominated by Proteobacteria , not Cyanobacteria , which implies a broad range of bacterial decomposition and nutrient recycling processes in addition to phototrophy. Principal component analysis of genes for light‐, nitrogen‐, and phosphorus‐related processes provided evidence of partitioning of mat function among taxonomically different constituents of the mat consortia. Viruses were also present (notably Alpha ‐, Beta ‐, Gammaproteobacteria phages and cyanophages), which likely contribute to cellular lysis and recycling, as well as other Bacteria, Archaea, and microbial eukaryotes. Nitrogen‐related genes were dominated by ammoniumassimilation systems, implying that the microbial mats are sites of intense mineralization, but not N‐oxidation, since nitrification genes were absent. Nutrient scavenging systems were detected, including genes for transport proteins and enzymes for converting larger molecules into more readily assimilated inorganic forms (allantoin degradation, cyanate hydrolysis, exophosphatases, phosphonatases). Metagenomic profiling results underscore the rich diversity of microbial life even in extreme polar habitats, and the capability of mat consortia to retain and recycle nutrients in the benthic microenvironment.

Saccharomyces cerevisiae strain UFMG 905 protects against bacterial translocation, preserves gut barrier integrity and stimulates the immune system in a murine intestinal obstruction model - Simone V. Generoso; Mirelle Viana; Rosana Santos; Flaviano S. Martins; José A. N. Machado; Rosa M. E. Arantes; Jacques R. Nicoli; Maria I. T. D. Correia; Valbert N. Cardoso (Archives of Microbiology, 2010)

Reappraisal of Macaca speciosa subfossilis from the Late Pleistocene of Northern Vietnam Based on the Analysis of Cranial Anatomy - Tsuyoshi Ito; Takeshi D. Nishimura; Brigitte Senut; Thomas Koppe; Jacque Treil; Masanaru Takai (International Journal of Primatology, 2009)

Proteins related to green algal striated fiber assemblin are present in stramenopiles and alveolates - John D. I. Harper; Jacques Thuet; Karl F. Lechtreck; Adrienne R. Hardham (Protoplasma, 2009)

Intussusception in the adult: an unsuspected case of Peutz–Jeghers syndrome with review of the literature - Jason D. Fraser; Steven E. Briggs; Shawn D. St. Peter; Giovanni De Petris; Jacques Heppell (Familial Cancer, 2009)

Physiological characterization of non-Saccharomyces yeasts from agro-industrial and environmental origins with possible probiotic function - Fabiana C. P. Tiago; Flaviano S. Martins; Carlos A. Rosa; Regina M. D. Nardi; Denise C. Cara; Jacques R. Nicoli (World Journal of Microbiology and Biotechnology, 2009)

Establishing the foundation for an applied molecular taxonomy of otters in Southeast Asia - Klaus-Peter Koepfli; Budsabong Kanchanasaka; Hiroshi Sasaki; Hélène Jacques; Kristina D. Y. Louie; Toanvong Hoai; Nguyen Xuan Dang; Eli Geffen; Arno Gutleb; Sung-yong Han; Thrine M. Heggberget; Lionel LaFontaine; et al. (Conservation Genetics, 2008)

Worldwide genotyping of castor bean germplasm (Ricinus communis L.) using AFLPs and SSRs - Gerard Allan; Amber Williams; Pablo D. Rabinowicz; Agnes P. Chan; Jacques Ravel; Paul Keim (Genetic Resources and Crop Evolution, 2008)

The effect on heart rate of combining single-dose fingolimod with steady-state atenolol or diltiazem in healthy subjects - John M. Kovarik; Michael Lu; Gilles-Jacques Riviere; Irene Barbet; Steve Maton; D. Ronald Goldwater; Robert L. Schmouder (European Journal of Clinical Pharmacology, 2008)

Post‐glacial migration of silver fir ( Abies alba Mill.) in the south‐western Alps - Serge D. Muller; Takeshi Nakagawa; Jacques‐Louis De Beaulieu; Mona Court‐Picon; Christopher Carcaillet; Cécile Miramont; Paul Roiron; Clément Boutterin; Adam A. Ali; Hélène Bruneton (Journal of Biogeography, 2007)
Aim Previous studies have failed to reconstruct the regional post‐glacial migration pattern of Abies alba in southern France. Based on the first exhaustive compilation of palaeoecological data in this region, we present the state‐of‐the‐art and attempt to synthesize the available information concerning glacial refugia and post‐glacial migration, and analyse the information with regard to climate and orography. Location South‐western Alps and adjacent areas, southern France. Methods The work compiles the available palaeoecological data in the south‐western Alps (52 sites, 290 radiocarbon dates). The post‐glacial migration pattern of Abies alba is reconstructed based on 22 selected palynological analyses (11 well‐dated reference sites and 11 supplementary ones). Results The geographical patterns of approaching area limit, immigration and expansion are reconstructed at the scale of the southern French Alps. Main conclusions Despite previous assertions, the evidence of refugia in southern France is non‐existent. The late‐glacial records of fir pollen, previously interpreted in French Mediterranean regions and on adjacent foot‐hills as possibly reflecting regional refugia, most probably correspond to reworking phenomena or long‐distance pollen transport. Fir migration, originating in the Apennine refugia and through the south‐western extremity of the Alps, was extremely rapid in the southern French Alps, only spanning a few centuries between 10,100 and 9800 cal. yr bp . The subsequent spread of fir populations was controlled by local parameters, such as the aridity of the inner valleys, which resulted in a delayed expansion in comparison to other regions. Abies almost disappeared from the south‐western Alps during the Roman era, around 2000 cal. yr bp .

The association of DNA sequence variation at the MAOA genetic locus with quantitative behavioural traits in normal males - Shai Rosenberg; Alan R. Templeton; Paul D. Feigin; Doron Lancet; Jacques S. Beckmann; Sara Selig; Dean H. Hamer; Karl Skorecki (Human Genetics, 2006)

Effect of regular exercise on homocysteine concentrations: the HERITAGE Family Study - Tomohiro Okura; Tuomo Rankinen; Jacques Gagnon; Suzanne Lussier-Cacan; Jean Davignon; Arthur S. Leon; D. C. Rao; James S. Skinner; Jack H. Wilmore; Claude Bouchard (European Journal of Applied Physiology, 2006)

Deformability characteristics of brazilian laterites - Jacques De Medina; Laura M. G. Motta; João D. G. Dos Santos (Geotechnical and Geological Engineering, 2006)

Verification and intercomparison of reactive transport codes to describe root-uptake - B. Nowack; K. U. Mayer; S. E. Oswald; W. van Beinum; C. A. J. Appelo; D. Jacques; P. Seuntjens; F. Gérard; B. Jaillard; A. Schnepf; T. Roose (Plant and Soil, 2006)

Earliest changes in the left ventricular transcriptome post-myocardial infarction - Mark H. Harpster; Somnath Bandyopadhyay; D. Paul Thomas; Pavel S. Ivanov; Jacque A. Keele; Natalia Pineguina; Bifeng Gao; Vijay Amarendran; Mark Gomelsky; Richard J. McCormick; Mark M. Stayton (Mammalian Genome, 2006)

Laplace–Dirichlet Energy Field Specification for Deformable Models. An FEM Approach to Active Contour Fitting - Jason D. Bayer; Jacques Beaumont; Andrzej Krol (Annals of Biomedical Engineering, 2005)

Antitumor and Anti-Pneumocystis Carinii Activities of Novel Bisbenzamidines - Jean Jacques Vanden Eynde; Annie Mayence; Melissa T. Johnson; Tien L. Huang; Margaret S. Collins; Sandra Rebholz; Peter D. Walzer; Melanie T. Cushion; Isaac O. Donkor (Medicinal Chemistry Research, 2005)

Hypomiltin, a novel azaphilone from Hypoxylon hypomiltum, and chemotypes in Hypoxylon sect. Hypoxylon as inferred from analytical HPLC profiling - Veronika Hellwig; Yu-Ming Ju; Jack D. Rogers; Jacques Fournier; Marc Stadler (Mycological Progress, 2005)

CD91 up-regulates upon immune stimulation in Xenopus adult but not larval peritoneal leukocytes - Shauna Marr; Ana Goyos; Jennifer Gantress; Gregory D. Maniero; Jacques Robert (Immunogenetics, 2005)

Recycling plant wax constituents for chemical defense: hemi-biosynthesis of triterpene saponins from ?-amyrin in a leaf beetle - Pascal Laurent; Cedric Dooms; Jean-Claude Braekman; Dsir Daloze; Jean-Louis Habib-Jiwan; Raoul Rozenberg; Arnaud Termonia; Jacques M. Pasteels (The Science of Nature, 2003)

Rooting blockage in the tobacco rac mutant occurs at the initiation phase, and induces diversion to xylem differentiation - Odile Faivre-Rampant; Jacques Dommes; Thomas Gaspar; Simone D'Angeli; Giuseppina Falasca; Maria Maddalena Altamura (Plant Biosystems, 2003)

Discovery of new chemical classes of synthetic ligands that suppress neuroinflammatory responses - D. Martin Watterson; Jacques Haiech; Linda J. Van Eldik (Journal of Molecular Neuroscience, 2002)

T cell receptor excision circles as markers for recent thymic emigrants: basic aspects, technical approach, and guidelines for interpretation - Mette D. Hazenberg; Martie C. Verschuren; Dörte Hamann; Frank Miedema; Jacques J. Dongen (Journal of Molecular Medicine, 2001)

Interstitial cells of Cajal in the striated musculature of the mouse esophagus - Jüri Rumessen; Alban de Kerchove d'Exaerde; Séverine Mignon; Florence Bernex; Jean-Pierre Timmermans; Serge Schiffmann; Jean-Jacques Panthier; Jean-Marie Vanderwinden (Cell and Tissue Research, 2001)

Taurine indirectly increases [Ca]i by inducing Ca2+ influx through the Na+-Ca2+ exchanger - Ghassan Bkaily; Doris Jaalouk; Sawsan Sader; Hadia Shbaklo; Pierre Pothier; Danielle Jacques; Pedro D'Orléans-Juste; Edward J. Cragoe; forename Bose (Molecular and Cellular Biochemistry, 1998)

Influence of the oxygen uptake slow component on the aerobic energy cost of high-intensity submaximal treadmill running in humans - Olivier Bernard; Frdric Maddio; Soualiho Ouattara; Chantal Jimenez; Annie Charpenet; Bruno Melin; Jacques Bittel (European Journal of Applied Physiology, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Endothelin-1 and insulin activate the steady-state voltage dependent R-type Ca2+ channel in aortic smooth muscle cells via a pertussis toxin and cholera toxin sensitive G-protein - Ghassan Bkaily; Radha Naik; Doris Jaalouk; Danielle Jacques; Demetri Economos; Pédro D'Orléans-Juste; Pierre Pothier (Molecular and Cellular Biochemistry, 1998)

Polymorphism in exon 10 of the human coagulation factor V gene in a population at risk for sickle cell disease - D. Helley; Claude Besmond; Rolande Ducrocq; F. da Silva; Marie-Claude Guillin; Annie Bezeaud; Jacques Elion (Human Genetics, 1997)

The use of confocal microscopy in the investigation of cell structure and function in the heart, vascular endothelium and smooth muscle cells - Ghassan Bkaily; Pierre Pothier; Pedro D'Orléans-Juste; May Simaan; Danielle Jacques; Doris Jaalouk; François Belzile; Ghada Hassan; Chantal Boutin; Georges Haddad; Witold Neugebauer (Molecular and Cellular Biochemistry, 1997)

Reflex adrenal medullary secretion during coronary occlusion mediated by cardiac receptors with afferent vagal fibres in the rat - D. Godin-Ribuot; Christophe Ribuot; Daniel Lamontagne; Nobuharu Yamaguchi; Réjean Couture; Jacques de Champlain; Pierre Demenge; Réginald Nadeau (Pflügers Archiv - European Journal of Physiology, 1997)

Refinement of the locus for autosomal dominant cerebellar ataxia type II to chromosome 3p21.1-14.1 - L. Krols; Jean-Jacques Martin; Gilles David; Nicole Van Regemorter; Ali Benomar; A. Lfgren; Giovanni Stevanin; Alexandra Drr; Alexis Brice; C. Van Broeckhoven (Human Genetics, 1997)